2018
DOI: 10.1038/s41598-018-29805-9
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis prevalence trends in adult women in 132 countries – estimations using the Spectrum Sexually Transmitted Infections model

Abstract: We estimated national-level trends in the prevalence of probable active syphilis in adult women using the Spectrum Sexually Transmitted Infections (STI) model to inform program planning, target-setting, and progress evaluation in STI control. The model fitted smoothed-splines polynomial regressions to data from antenatal clinic surveys and screening and representative household surveys, adjusted for diagnostic test performance and weighted by national coverage. Eligible countries had ≥1 data point from 2010 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 36 publications
5
57
0
3
Order By: Relevance
“…Syphilis prevalence is increasing in many countries . Untreated syphilis in pregnant women is a major cause of foetal death and congenital infection .…”
Section: Resultsmentioning
confidence: 99%
“…Syphilis prevalence is increasing in many countries . Untreated syphilis in pregnant women is a major cause of foetal death and congenital infection .…”
Section: Resultsmentioning
confidence: 99%
“…We found that FSWs who had attended up to the primary school showed a significantly higher prevalence of syphilis positivity. This may reflect the low overall awareness of these individuals about the risks involved and sex work and measures to prevent STIs [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…[4] According to 2012 report, the global prevalence of syphilis in adult men and women were 0.49% (0.4-0.6%) and 0.48 (0.3-0.7%). [5] According to 2019 report, the global prevalence of malaria was estimated to be 219 million cases. [6] Blood consists of different blood cells suspended in plasma.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%